2000
DOI: 10.1159/000007005
|View full text |Cite
|
Sign up to set email alerts
|

Transvenous Pacemaker Leads Do Not Worsen Tricuspid Regurgitation: A Prospective Echocardiographic Study

Abstract: Limited prospective data are available regarding the influence of pacemaker leads on tricuspid valve function. To examine the true incidence of these complications, 35 patients were prospectively examined by two-dimensional and Doppler echocardiography before and after implantation of either a permanent pacemaker or an automatic implantable cardioverter-defibrillator. Of the 35 patients imaged preoperatively, the amount of tricuspid regurgitation (TR) was judged as normal or trivial in 15 (43%), mild in 10 (29… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
59
1
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 7 publications
(8 reference statements)
5
59
1
3
Order By: Relevance
“…It has been previously described in adults in the setting of transvenous pacemaker leads (4)(5)(6). The purpose of this study was to determine whether transvenous pacemaker leads are associated with increased echocardiographic findings of tricuspid regurgitation.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…It has been previously described in adults in the setting of transvenous pacemaker leads (4)(5)(6). The purpose of this study was to determine whether transvenous pacemaker leads are associated with increased echocardiographic findings of tricuspid regurgitation.…”
Section: Introductionmentioning
confidence: 96%
“…A retrospective study of 374 adults after transvenous pacemaker lead placement across the TV showed increased prevalence of significant TR when compared with age and sex-matched controls (5). However, one prospective study suggested that transvenous pacemaker leads do not exacerbate TR (6).…”
Section: Introductionmentioning
confidence: 99%
“…D.W. Leibowitz еt al. не обна-ружили никаких существенных изменений в степени TР в раннем послеоперационном пе-риоде у 35 пациентов с ЭКС, при этом у 6 из них было отмечено улучшение эхокардиогра-фической картины после имплантации, воз-можно, связанное с изменением гемодинами-ки, снижением давления в правых камерах [36]. Тем не менее большинство исследований про-демонстрировали появление клапанной несо-стоятельности через несколько лет после им-плантации ЭКС, с единичными случаями вы-раженного ухудшения.…”
Section: Discussionunclassified
“…Morgan et al при анализе ТР у 20 больных через 6 мес после имплантации ААУ, где также не было выявлено значимого измене-ния функции ТК [20]. Неожиданные результаты были получены D.W. Leibowitz et al при оцен-ке функции ТК в раннем послеоперационном периоде после имплантации ААУ [21]. У 6 паци-ентов из 35 было отмечено уменьшение ТР на 2-й день после имплантации устройства.…”
Section: имплантация антиаритмических устройств является методом выбоunclassified
“…Chan обратили внимание на значительное количество ограничений в боль-шинстве упомянутых исследований, включая ретроспективный характер, незначительное число пациентов, недостаточное количество предоставленных исходных данных, получен-ных до имплантации ААУ, отсутствие единой системы оценки степени регургитации на ТК и значительные различия во временном интер-вале наблюдения за больными в послеопера-ционном периоде в разных работах [25]. По мне-нию авторов, этим обусловлена противоречи-вость данных, полученных в ходе этих исследований [10,12,16,[17][18][19]21].…”
Section: имплантация антиаритмических устройств является методом выбоunclassified